Occurrence of a Mixed Mycoplasma and Moraxella Infection Associated with a Severe Eye Keratoconjunctivitis of Bovine - A.Raman; R. Durairajan; J. Ramesh (The Indian Veterinary Journal, 2024)
Mycoplasma and Moraxella gene were both detected from conjunctival swabs taken from young dairy cattle showing symptoms consistent with keratoconjunctivitis. Based on laboratory tests and clinical observations, the first phase of the disease was likely pneumonic in nature, possibly caused by bovine respiratory syncytial virus. Bacterial cause of keratoconjunctivitis in bovine may be due to Infectious bovine rhino tracheitis (IBRT), Moraxella bovis, Mycoplasma conjunctivae, etc. An investigation carried out at R.Kunnathur, Tiruvannamalai district during the month of February 2022, Tamil Nadu, India revealed presence of Mycoplasma and Moraxella in bovine (n=100 animals). The investigation of eye swabs from affected animals showed that the presence of bacteria such as Moraxella spp and Mycopalsma spp. by genus specific polymerase chain reaction (PCR) of the isolate was positive for Moraxella spp. and Mycoplasma spp. This study reports the presence of mixed eye infection in dairy farming warranting further studies to know the exact status of this organism so as to prevent keratoconjunctivitis in bovine.